Hubungan Peran Keluarga Dengan Pengendalian Kadar Gula Darah Pada Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Pauh Padang: The Relationship between Family Role and Blood Sugar Level Control in Diabetes Mellitus Patients in the Working Area of the Pauh Padang Health Center - Honesty Putri; Fitra Yeni; Tutwuri Handayani (NERS Jurnal Keperawatan, 2013)
Diabetes mellitus is a chronic metabolic disease or disorder with multietiologi characterized by high blood sugar levels (hyperglycemia). Diabetes mellitus can not be cured but can be controlled by regulating blood sugar levels. One of important factor in controlling blood sugar levels is the family role. The purpose of this study was to determine relation between family role with blood sugar levels in diabetes mellitus patients at the working area of Pauh Health Center Padang 2013. The study was a descriptive analytic with cross sectional approach. were taken with simple random sampling technique. Data were analyzed using univariate descriptive statistical form frequency distributions and bivariate analysis performed by chi-square test with a significance level of α 0.05. The results showed 53.3% of respondents had an unfavorable role of the family in patients with diabetes mellitus, 57.8% with abnormal blood sugar levels. The results of the bivariate analyzes indicate that there is a significant relationship between the role of family ties with the blood sugar levels in patients with diabetes mellitus (p <0.05). Based on the results, the role of the family has a role in controlling blood sugar levels. Therefore expected to increase family participation in care and to motivate patients with diabetes mellitus in controlling blood sugar levels so that blood sugar levels under controlled conditions.